Prediction of early-age creep and cracking age of concrete: a proposed modification for AS3600 provisions. Issue 2 (3rd May 2016) - Khan, Inamullah; Castel, Arnaud; Gilbert, Raymond Ian
Abstract: Early-age thermal and shrinkage-induced cracking is a major problem in concrete structures. The risk of early-age thermal cracking is increased if the degree of restraint to early-age contraction is increased. At this early age, tensile creep plays a key role in relaxing shrinkage-induced stresses and delaying the time to cracking. However, limited data are available concerning tensile creep of concrete and the magnitude and rate of development of the early-age shrinkage of Australian concrete. As a consequence, tensile creep is often poorly modelled in predictions of early-age cracking. The current method to calculate creep in the Australian Standard AS3600 is based on compressive creep data obtained from specimens loaded at ages generally greater than 14 days and cannot be used to predict very early-age creep confidently. In order to accurately quantify the early-age shrinkage and creep of concrete, a comprehensive experimental programme is being conducted at the UNSW Centre for Infrastructure Engineering and Safety. Creep and shrinkage strains were measured on different specimens subjected to sustained loading. Tests were conducted on two different concrete mixes of normal strength concrete (32 and 45 MPa). Restrained ring specimens were tested to observe the cracking age of concrete. A model is proposed to predict the early-age tensile creep of concrete.